Electrocatalytic activity of electrochemically dealloyed PdCu3 intermetallic compound towards oxygen reduction reaction in acidic media. Issue 30 (18th July 2018) - Gunji, Takao; Noh, Seung Hyo; Ando, Fuma; Tanabe, Toyokazu; Han, Byungchan; Ohsaka, Takeo; Matsumoto, Futoshi
Abstract : A structurally ordered phase of PdCu3 nanoparticles (NPs)/carbon black (CB), in which PdCu3 has a Cu3 Au-type structure, was prepared by co-reduction of Pd and Cu precursors using ethylene glycol as a reducing agent and an annealing procedure. Abstract : A structurally ordered phase of PdCu3 nanoparticles (NPs)/carbon black (CB), in which PdCu3 has a Cu3 Au-type structure, was prepared by co-reduction of Pd and Cu precursors using ethylene glycol as a reducing agent and an annealing procedure. The obtained catalysts were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), energy-dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). The XRD and STEM measurements enabled us to confirm the crystal structures of both atomically disordered Pd–Cu NPs/CB and ordered intermetallic PdCu3 NPs/CB. From the TEM and EDS measurements, it was found that PdCu3 NPs are uniformly dispersed on the CB surface and the atomic ratio of Pd to Cu is 25.3 : 74.7. DFT calculations suggested that the PdCu3 NPs have a uniformly ordered structure of Pd and Cu and that Cu-free surface-structured PdCu3 NPs, which are formed by so-called electrochemical dealloying, i.e., the dissolution of surface and sub-surface Cu in the ordered PdCu3 structure, exhibit superior electrocatalytic activity in the ORR in comparison with Pd NPs/CB. This catalytic activity can be explained reasonably on the basis of the measured value of the d-band center and theoretical calculations of catalyst–oxygen binding energies. Interestingly, the surface of electrochemically dealloyed PdCu3 has a lower oxygen binding energy than the Pt (111) surface ( i.e., the oxygen binding energy of PdCu3 was significantly decreased by electrochemical dealloying). We have found a Pd-based catalyst of which the electrocatalytic activity in the ORR may exceed that of Pt-based catalysts according to DFT calculations. In addition, the potential of PdCu3 NPs/CB as a cathode catalyst in direct methanol fuel cells is discussed briefly.